Wynagrodzenia małżonków i kohabitantów - Stolarska, Barbara (Annales. Etyka w Życiu Gospodarczym, 2013)
It is often believed that marriage and cohabitation do not lie in the area of interest of economics. However, a trial of economic analysis of romantic relationships is possible and leads to interesting conclusions. Researchers from Western Europe, such as Cohen (2003), Richardson (2000), and Stratton (2002), suggest that not only the choice of romantic partner but also the form of our relationship is crucial. The issue of a relationship’s legalisation has a big impact on the quality and persistence of union as well as on the level of earnings of the couple. Husbands get a, so called, ‘marriage premium’ – they earn more than informal partners. In Polish literature the topic of marriage and cohabitation is analysed very rarely. The aim of the thesis is to discuss differences between the earnings of spouses and cohabitating partners and to present the results of research conducted, which suggest that marriage is related to a higher level of earnings. As the analyses presented show, cohabitation has become a serious issue for present society. We should decide whether the growing popularity of informal relationships should be stopped. It seems that cohabitation is ethically doubtful due to its negative impact on couples as well as on the whole of society